Adherence to guidelines in the management of patients with chronic heart failure follow-up: role of periodic echocardiographic examinations. Issue 3 (March 2020) - Bosso, Giorgio; Valvano, Antonio; Guarnaccia, Franco; Fimiani, Biagio; Carbone, Vincenzo; Cittadini, Antonio; Zito, Giovanni Battista; Oliviero, Ugo
Abstract : Background and aim: The Adherence to Guidelines in the Treatment of patients with Chronic Heart Failure trial showed a poor adherence to the current therapeutic guidelines in 660 chronic heart failure (CHF) patients. The second phase, Adherence to Guidelines in the Treatment of patients with Chronic Heart Failure follow-up, was aimed to determine if periodic echocardiographic evaluations could improve the prognosis of CHF patients and/or increase the adherence to the guidelines. Material and methods: Among 528 CHF patients with reduced ejection fraction from the ALERT registry, 436 patients accepted to participate in the second phase of the study between February and September 2013 and completed the 3-year follow-up phase between February and September 2016. They were randomized into two groups: Group A ( n  = 218) followed by clinical evaluation and ECG every 3 months, and echocardiography every 6 months and Group B ( n  = 218) monitored only with clinical evaluation and ECG every 3 months. Results: The number of vascular events that occurred resulted as similar in both the groups: there were 78 hospitalizations (37 in Group A vs. 41 in Group B); 9 home-treated vascular events (4 in Group A and five in Group B); and 16 cardiovascular deaths (9 and 7, respectively). The adherence to the guidelines at the end of the trial resulted as significantly improved in both the groups in comparison with the basal evaluation, without differences between the two groups. Conclusion: A strict follow-up of CHF patients was associated with a lower number of events and an improvement in the adherence to the guidelines. Periodic echocardiography does not modify these results.